The Influence of Accreditation, Promotion, Location, and Facilities on Decision-Making in Choosing the S1 Management Study Program at Widyatama University - Darajat, Zakiah; Widuri Sakti, Intan (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This research aims to determine the extent to which accreditation, promotion, location, and facilities provided by Widyatama University influence prospective students' decisions in choosing the Bachelor's Degree in Management program. Widyatama University is one of the private universities in Bandung that offers diploma, bachelor's (S1), applied bachelor's (D4), and postgraduate (S2 and S3) programs. The S1 Management Study Program is one of the programs that has a high appeal among prospective students. This research uses a descriptive method with a quantitative approach. The data analysis technique was conducted using multiple linear regression. The respondents in this study amounted to 69 people who were selected through purposive sampling, consisting of active students from Widyatama University. Based on the data analysis results, it was found that the four independent variables (Accreditation, Promotion, Location, and Facilities) simultaneously have a significant influence on prospective students' decisions in choosing the S1 Management Study Program, with a Sig. value of (0.000) < α (0.05). The partial test results show that the Location variable (X3) and Facilities variable (X4) have a significant influence on prospective students' decisions, with Sig. values of each < 0.05. The Accreditation variable (X1) and Promotion variable (X2) also have an influence, although less significant compared to the other variables. This research emphasizes the importance of enhancing digital-based promotion strategies, improving campus facilities, and program accreditation to attract more prospective students